The Control Actions Structure Optimization in the Process of the Regions Housing and Communal Services Development - Asiyat K. Dorgushaova; Vladimir I. Zarubin; Saida K. Kuizheva; Tatiana A. Ovsyannikova; Elena N. Klochko (International Journal of Economics and Financial Issues, 2016)
The purpose of the present research is to find areas of organizational and economic mechanisms that enhance the efficiency of regional utilities. A systematic approach to the analysis of the organizational and economic mechanism of Housing in the region, provides a systematic, comprehensive and effective investigation. Strategic Imperatives in the management of regional utilities are defined taking into account the crisis tendencies in the process of its development. Case utilities management is seen as the realization of the objectives of its development in different scenario conditions. With the help of mathematical modeling methods and parameters are determined by the structure of the control actions. The article proposes a methodology for calculating the article options strategy utilities management in the region, the results of modeling the trajectory of housing and communal services of the Republic of Adygea.